If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 56 + -9t Solving 2 = 56 + -9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '9t' to each side of the equation. 2 + 9t = 56 + -9t + 9t Combine like terms: -9t + 9t = 0 2 + 9t = 56 + 0 2 + 9t = 56 Add '-2' to each side of the equation. 2 + -2 + 9t = 56 + -2 Combine like terms: 2 + -2 = 0 0 + 9t = 56 + -2 9t = 56 + -2 Combine like terms: 56 + -2 = 54 9t = 54 Divide each side by '9'. t = 6 Simplifying t = 6
| -35+4/15 | | 13x+30=23x-15 | | 0.35s+0.6(30-s)=0.45(30) | | 26-9x=3x-1 | | 9-6x/7=16 | | 12(3x+3)-7(2x-6)=2x-42 | | 6-3x-5x-10x+18-12= | | p-16=51 | | -7/2*10 | | 2(5x-3)-2x-4=5-(6x+1) | | -9-6x/7=16 | | 0.20x+0.05(10-x)=0.10(14) | | -27=n-20 | | 14-3(x-2)=x+16 | | 2a+7=50 | | -7/2-1/4 | | -7/10t=1/8 | | (43-7x)+(83-11x)=(117-22x) | | x^2-12x-16=0 | | c+160=1780 | | c=1/2(s+b)2 | | 0.8(x+4)-0.3x=1.7 | | (x-4)(x+2)(x+2)=0 | | 4(x+8)=-4(x-4) | | 3k+k-4/9=1/3 | | 2x+4-5(x+1)=4x+5 | | x^4/3=1296 | | -x^2+17x+45=0 | | c=1/2(s+b)f | | 7-5v+10= | | 4x=10x-3 | | 0.25x^2-10x+64=0 |